溶融Fe-Cr-Ni合金におけるAl脱酸平衡の実験的測定と数値解析 - Fukaya, Hiroshi; Nakajima, Seika; Gamutan, Jonah; Suzuki, Shigeru; Kajikawa, Koji; Saito, Ken; Miki, Takahiro (Nippon Tekko Kyokai, 2022)
The aluminum deoxidation equilibrium in molten Fe-10 to 40 mass%Cr-8 mass%Ni and Fe-18 mass%Cr-8 to 30 mass%Ni alloys was experimentally determined at 1 873 K and 1 773 K to obtain the thermodynamic parameters at both temperatures, corresponding to the refining and casting processes, respectively. Thermodynamic analysis on Al deoxidation was carried out based on the sub-regular solution model using a Redlich–Kister type polynomial. Fe–Al, Ni–Al, Cr–Al and Fe–Cr–Ni interaction parameters were obtained from experimental results and a thermodynamic assessment. Using these parameters, the Al deoxidation equilibrium over the complete composition range of the Fe–Ni alloy and in more than 50 mass%Fe of the Fe–Cr and Fe–Cr–Ni alloys can be calculated for the temperature ranges of both of the refining and casting processes.